Mekanisme Pertahanan Ego Tokoh Zenchi Naigu Dalam Cerpen Hana Karya Akutagawa Ryunosuke - Aditya, I Wayan Deva; Antartika, I Kadek; Sadyana , I Wayan (STKIP AGAMA HINDU SINGARAJA, 2024)
This research aims to describe the forms of ego defense mechanisms from the character named Zenchi Naigu in the short story